2005
DOI: 10.1207/s15324796abm3001_7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized pilot of a self-guided internet coping group for women with early-stage breast cancer

Abstract: These results demonstrate the potential efficacy of self-guided Internet coping groups while highlighting the limitations of such groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(212 citation statements)
references
References 38 publications
5
204
2
1
Order By: Relevance
“…Thus far, positive outcomes have been reported in RCTs of Internet interventions across a wide range of clinical outcomes, including asthma management (20,30,59,74,111), caregiving stress (84,85), breast cancer coping (104,157), chronic pain (13,14,15,45,54), congestive heart failure symptom monitoring (4,64,117), diabetes self management (5, 8, 11, 21, 50, 65-68, 75, 89-91), problem drinking (77,86,148), falls prevention (160), headache management (31,125,132), multiple risk behavior change (76), cardiac rehabilitation (126), HIV prevention (12,63,141), medical decision making (7,16,72), cognitive stimulation in Alzheimer's (136) (32,151), tinnitus distress (3), and weight loss (44, 56, 58, 92, 118, 121, 137-139, 152, 154, 155).…”
Section: Do Internet Interventions Work?mentioning
confidence: 99%
“…Thus far, positive outcomes have been reported in RCTs of Internet interventions across a wide range of clinical outcomes, including asthma management (20,30,59,74,111), caregiving stress (84,85), breast cancer coping (104,157), chronic pain (13,14,15,45,54), congestive heart failure symptom monitoring (4,64,117), diabetes self management (5, 8, 11, 21, 50, 65-68, 75, 89-91), problem drinking (77,86,148), falls prevention (160), headache management (31,125,132), multiple risk behavior change (76), cardiac rehabilitation (126), HIV prevention (12,63,141), medical decision making (7,16,72), cognitive stimulation in Alzheimer's (136) (32,151), tinnitus distress (3), and weight loss (44, 56, 58, 92, 118, 121, 137-139, 152, 154, 155).…”
Section: Do Internet Interventions Work?mentioning
confidence: 99%
“…Other recent studies with breast cancer patients have shown mixed or negative results. (Edelman et al, 1999;Edmonds et al, 1999;Scholten et al, 2001;Owen et al, 2005). However, none of these trials used a specialised breast nurse.…”
Section: Previous Research On Psycho-educational Interventions With Pmentioning
confidence: 99%
“…21 In a large sample of the impact of social networking on breast cancer survivors, each additional member in a given person's social network independently predicted higher quality of life. 22 Social networking components are likely to motivate those with cancer to participate in online communities [23][24][25] and have been linked with positive health outcomes. 26,27 Given the popularity of sites, such as Facebook, there is a high level of user demand for social networking features in eHealth interventions, and understanding how to marry these features with established eHealth intervention components has substantial promise for increasing the efficacy of these kinds of interventions.…”
mentioning
confidence: 99%